PENGARUH FAKTOR INTERNAL DAN EKSTERNAL PERUSAHAAN TERHADAPAUDIT DELAY PADA PERUSAHAAN TELEKOMUNIKASI DAN TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2010-2012 - Riska Anggraini; Rita Anugerah; Susilatri - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The objective of this research is to examine the influence of internal factors (firm size, profitability, solvability, internal control system) and external factor ( public accountant size) on the audit delay at a telecommunication and transportation companies listed in Indonesia Stock Exchange in 2010 until 2012. Sample was selected by using purposive sampling method, and data analysed used multiple regression method. The result of research shows that audit delay is significantly influenced only by profitability with significant value 0.000, and the variable firm size, solvability, internal control system, and public accountant size were not significantly influenced of the audit delay.Adjusted R2 is a 36.3%, which means that variable firm size, profitability, solvability, internal control system, and public accountant size just explains 36.3% of audit delay variable.Keywords: audit delay, firm size, profitability, solvability, internal control system, public accountant size.